TRACE: An Unbiased Method to Permanently Tag Transiently Activated Inputs - Krauth, Nathalie; Khalil, Valentina; Jariwala, Meet; Mermet-Joret, Noemie; Vestergaard, Anne-Katrine; Capogna, Marco; Nabavi, Sadegh (Frontiers in Cellular Neuroscience, 2020)
A fundamental interest in circuit analysis is to parse out the synaptic inputs underlying a behavioral experience. Toward this aim, we have devised an unbiased strategy that specifically labels the afferent inputs that are activated by a defined stimulus in an activity-dependent manner. We validated this strategy in four brain areas receiving known sensory inputs. This strategy, as demonstrated here, accurately identifies these inputs.